2022
DOI: 10.3390/microorganisms10020222
|View full text |Cite
|
Sign up to set email alerts
|

Into the Unknown: Microbial Communities in Caves, Their Role, and Potential Use

Abstract: Caves have been an item of amateur and professional exploration for many years. Research on the karst caves has revealed great diversity of bacteria, algae, and fungi living on stone walls and speleothems, in mud puddles or sediments. They have become the source of interest for various research groups including geologists, chemists, ecologists, or microbiologists. The adaptations of cave-dwelling organisms applied to their survival are complex and some of their properties show potential to be used in various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 125 publications
0
12
0
Order By: Relevance
“…At present, cave microbiology belongs to a new field in biology and geology. A large part of various and numerous cave ecosystems has not been studied, and the diversity and functional potentials of cave microorganisms remain to be explored by both culture-dependent and -independent methods [ 60 ]. In our study, while understanding the diversity of bacteria in the silicate cave, we also suggested bacterial functions in rock transformation, particularly the formation/dissolution of speleothems; in addition, we aim to elucidate archaeal functions in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…At present, cave microbiology belongs to a new field in biology and geology. A large part of various and numerous cave ecosystems has not been studied, and the diversity and functional potentials of cave microorganisms remain to be explored by both culture-dependent and -independent methods [ 60 ]. In our study, while understanding the diversity of bacteria in the silicate cave, we also suggested bacterial functions in rock transformation, particularly the formation/dissolution of speleothems; in addition, we aim to elucidate archaeal functions in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are land, ice, volcanic and sea caves, and, as mentioned above, most of them are composed of limestone, gypsum and dolomite rocks. Aragonite, selenite, sodium and magnesium sulfates, limonite, etc., are also sometimes found [3].…”
Section: Cave Ecosystemmentioning
confidence: 95%
“…In the cave environment there is darkness, constant temperature, high humidity, low pressure, low oxygen concentration and minimal nutrients. It is divided into three zones: the bright entrance zone, which is approximately five meters long, with similarities to the outside environment; the twilight zone, which is approximately ten to twenty meters long, with less sunlight, no vegetation and a relatively constant temperature; and the dark zone, which is without light and has an absolutely constant temperature [3]. This unique climatic stability makes caves ideal environments for the study of climate change in nature.…”
Section: Cave Ecosystemmentioning
confidence: 99%
“…The most significant detergents are Bryobacter , Chroococcidiopsis , Rubrobacter , Blastocatella , Sphingomonas and Loriellopsis , where the investigation of phototrophic biofilms revealed the existence of many predators operating naturally to regulate the growth of photosynthetic-based biofilms in caves ( De Leo and Jurado, 2021 ). Kosznik-Kwasnicka et al (2022) investigated the caves and discovered a wide variety of bacteria, algae, and fungi dwelling on stone walls and develop inside the rock, where black fungi are one of the most threatening risks to the stone cultural heritage of the Mediterranean basin. The black fungus’s capacity to generate a chemical effect on carbonate stones and affect other materials/historical artifacts by the creation of acid, cellulase, esterase, and protease, so the possibility of using them as reference organisms were made by the achievement of their sensitivity to four conventional biocides ( Isola et al, 2022 ).…”
Section: Conservation Of Inorganic Deteriorated Archaeological Objectsmentioning
confidence: 99%